SolarWinds Attack: Stages, Implications, and Mitigation Strategies in the Cyber Age - Gia Anisa; Fitria Widianingsih (Yayasan Asmin Intelektual Berkah, 2024)
SolarWinds is a software company based in the United States that provides IT monitoring and management tools. Founded in 1999, SolarWinds offers a variety of products that help organizations manage networks, systems, IT infrastructure, applications and cloud-based services. SolarWinds products are used for performance monitoring, log management, IT security, and data analysis. The company became widely known after a major cybersecurity incident came to light in late 2020, in which their network management software, Orion, was used as a vector for attacks by a state-backed hacking group. These attacks affected many organizations, including government agencies and private companies, and led to an increased focus on software supply chain security. This paper has reviewed stages, Implications, and mitigation strategies of SolarWinds.